Expression Of Osteoblasts In Periodontitis With Material Preservation Pocket Technique Gengigel® (Hyaluronic Acid 0.2%) - Dwi Wahyu Indrawati; Ernie Maduratna Setyawatie; A. Retno Pudji Rahayu; Rizky Briliant Syah Manurung; Anis Khoirin Hayati (Eduvest - Journal of Universal Studies, 2024)
Hyaluronic acid as a socket preservation material can absorb large amounts of hydration and regulate appropriate pressure in the surrounding tissue, resulting in expansion of the extracellular space. The socket preservation technique used is a solution to bone loss due to tooth extraction. However, research on the hyaluronic acid (Gengigel) material in sockets with periodontitis has not yet been clearly studied. In this study, we will see an increase in the number of osteoblasts in the alveolar bone after tooth extraction in Wistar rats with periodontitis. To determine the increase in the number of osteoblasts after administering Hyaluronic acid to the tooth sockets of Wistar rats with periodontitis. An increase in the number of osteoblast cells was observed using a multi-head light microscope in 5 areas of the preparation at 400x magnification. The measurement results from 5 areas are averaged and a calculation is obtained for one preparation. There are 2 groups that will be used in this research, namely the Control group (without treatment), HA (given Gengigel). Each group was tested at 14 and 21 days after administering the material. The research results showed that the Hyaluronic Acid (Gengigel) group had a higher number of osteoblast cells than the control group. The one-way ANOVA test showed an average significance result of 0.000 (p < 0.05) for all groups. This indicates that there was a significant change in each treatment group. Giving hyaluronic acid to the tooth sockets of Wistar rats with periodontitis can increase the number of osteoblast cells.